THE BLACKCHIN TILAPIA: BASIC CHARACTERISTIC FEATURES - admin, admin; ANWA-UDONDIAH, E. P. (Nigerian Journal of Fisheries, 2011)
An investigation was conducted into the basic characteristic features of the blackchin tilapia, Sarotherodon melanotheron (Rüppell, 1852). Adult male S. melanotheron was caught from an artificial body of water (burrow-pit) at the experimental fish farm of Nigerian Institute for Oceanography and Marine Research (NIOMR) at Badore, Lagos State. The male fish released its fry from the mouth when it was introduced into a basin containing water. The released fry were transferred to an out-door hatchery and acclimatized for a week in fibre-glass tanks. Observations of changes in the external features of the fish as they grew were noted and recorded over a period of six months. The fry averaging 9.70 standard length and 11.70 total length in size were silvery in colour and possessed seven bars of darker coloration on the flanks. The black melanic pigmentation on or around the chin observed in the third month is an important aid in species identification. The initial difficulty in identifying the specific tilapia studied due to the adaptive powers of colour change of the parent fish and the variable pigmentations that increased in number as the young grew necessitated this paper.